Stromal Clues in Endometrial Carcinoma: Loss of Expression of β-Catenin, Epithelial-Mesenchymal Transition Regulators, and Estrogen-Progesterone Receptor. (May 2016) - Senol, Serkan; Sayar, Ilyas; Ceyran, Ayse B.; Ibiloglu, Ibrahim; Akalin, Ibrahim; Firat, Ugur; Kosemetin, Duygu; Engin Zerk, Pinar; Aydin, Abdullah
Abstract : Epithelial-stroma interactions in the endometrium are known to be responsible for physiological functions and emergence of several pathologic lesions. Periglandular stromal cells act on endometrial cells in a paracrine manner through sex hormones. In this study, we immunohistochemically evaluated the expression of epithelial-mesenchymal transition regulators (SNAIL/SLUG, TWIST, ZEB1), adhesion molecules (β-catenin and E-cadhenin), estrogen (ER)-progesterone (PR) receptor and their correlation with each other in 30 benign, 148 hyperplastic (EH), and 101 endometrioid-type endometrial carcinoma (EC) endometria. In the epithelial component, loss of expression in E-cadherin, ER and PR, and overexpression of TWIST and ZEB1 were significantly higher in EC than in EH ( P <0.01). In the periglandular stromal component, β-catenin and SNAIL/SLUG expression were significantly higher in normal endometrium and simple without atypical EH compared with complex atypical EH and EC ( P <0.01). In addition, periglandular stromal TWIST expression was significantly higher in EH group compared with EC ( P <0.05). There was significantly negative correlation between β-catenin and ER, TWIST and ER, and TWIST and PR in hyperplastic and carcinomatous glandular epithelium, whereas there was a significantly positive correlation between β-catenin and SNAIL-SLUG, β-catenin and TWIST, β-catenin and ER, β-catenin and PR, SNAIL-SLUG and ER, SNAIL-SLUG and PR, TWIST and ER, TWIST and PR, in periglandular/cancer-associated stromal cells ( P <0.01). In conclusion, the pattern of positive and negative correlations in the expression of epithelial-mesenchymal transition regulators (SNAIL-SLUG and TWIST), sex hormone receptors (ER and PR), and β-catenin between ECs and hyperplasia, as well as between epithelium and stroma herein, is suggestive of a significant role for these proteins and their underlying molecular processes in the development of endometrial carcinomas. Abstract : Supplemental Digital Content is available in the text.